Potential Impact of Disposable Mask Garbage Pollution in Cinere District - Khairun Nisa; Dwi Nowo Martono; Haruki Agustina (Jurnal Penelitian Pendidikan IPA, 2023)
At present, disposable masks have become a necessity and habit for the general public. This causes an increase in the volume of single-use mask waste generation. If disposable mask waste is not managed properly and correctly it can harm living things such as fauna and contains micro plastics which have the potential to be a source of pollution in the environment. This study aims to analyze the potential impact of household-scale disposable mask waste pollution in Cinere District. The method used in this research is statistics and literature study. The results showed that the average use of disposable face masks in Cinere District was 2 pieces/day with a weight of 3.54 grams and it was estimated that the people of Cinere District produced 76,494 disposable masks waste/day with an extrapolation of the potential impact of micro plastic pollution reaching 67.31 billion/day which will be released into the environment. This will be a heavy burden on the environment, therefore good cooperation is needed between the community and the government in managing disposable mask waste on a household scale in order to reduce and prevent pollution of disposable mask waste in the environment.